Underutilized crops for diversified agri-food systems: spatial modeling and farmer adoption of buckwheat in Italy - Verza, Marta; Camanzi, Luca; Mulazzani, Luca; Giampaolo, Antonio; Rodriguez, Santiago; Malorgio, Giulio; Mattas, Konstadinos (Frontiers in Sustainable Food Systems, 2025)
The widespread standardization of agri-food systems through monoculture practices has resulted in biodiversity loss and reduced ecosystem resilience. Incorporating underutilized crops such as buckwheat into crop rotations offers a viable strategy to enhance biodiversity, improve soil health, and foster more sustainable and resilient agricultural systems. This study examines the potential adoption of buckwheat in Italy and analyzes its economic viability across different crop rotations. It evaluates how factors such as financial incentives, peer influence, and farmers’ willingness to adopt affect the diffusion of this underutilized crop. To this end, a spatial agent-based model (ABM) is employed to simulate farmers’ decision-making processes based on profit maximization and peer influence. The model evaluates two diffusion scenarios (traditional and expansion) alongside two levels of willingness to adopt (high and low), comparing the profitability of traditional crop rotations with rotations that include buckwheat across nine Italian regions. The results revealed that while increased contract prices can incentivize buckwheat adoption, financial incentives alone are insufficient to generate widespread adoption, particularly when the willingness to adopt is low. Peer influence and intrinsic motivation emerged as key drivers, highlighting the need for strategies beyond monetary incentives. These findings suggest that policies should combine financial support with initiatives that foster knowledge-sharing, educational outreach, and improved supply chain integration. The study provides a framework for evaluating the adoption of other underutilized crops and emphasizes the need for further research on risk aversion, environmental variability, and broader supply chain interactions to refine adoption strategies.